Torus knots that cannot be untied by twisting - Yasuhara, Akira; Ait Nouh, Mohamed (Revista Matemática Complutense, 2001)
We give a necessary condition for a torus knot to be untied by a single twisting. By using this result, we give infinitely many torus knots that cannot be untied by a single twisting.